Analysis of coral reef health based on the abundance of herbivorous reef fish in the waters of Krueng Raya, Aceh Besar - Ulfah Maria; Cindy Safitri Arsa; Andianto Dika; Zahra Avifah; Miswari Nur (BIO Web of Conferences)
The health and sustainability of coral reefs are influenced by the complex interactions of various organisms, and one indicator of their health is the presence of herbivorous reef fish. This study aims to analyze the health of coral reefs based on the abundance of herbivorous reef fish in the waters of Krueng Raya, Aceh Besar. The research was conducted in October 2023 at three stations. Data collection was carried out using the Point Intercept Transect (PIT) method for coral monitoring, while the herbivorous fish were assessed using the Underwater Visual Census (UVC) Belt Transect method. The results showed that the abundance of herbivorous reef fish ranged from 1597.92 ind/ha to 5918.18 ind/ha, with a total of families, 12 genera, and 25 species of herbivorous reef fish identified. The percentage of algae cover ranged from 4.65% to 35.55%. This study indicates an inverse relationship between the abundance of herbivorous reef fish and algae cover. As the abundance of herbivorous reef fish increases, the percentage of algae cover decreases.